Azerbaijan and its oil resources: Curse or blessing? - Farid Zulfigarov; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2019)
We examine the relationship between oil price fluctuations and economic activity in Azerbaijan using vector autoregressive models for the period 2002Q1-2018Q4. Our key results are as follows. First, quarterly GDP growth decreases after oil price innovations in both, the oil and gas sector and in the remaining economy. Downturns (upswings) in the oil and gas sector also prompt downturns (upswings) in the non-oil sector as fluctuations in oil revenues affect the government's capacity to subsidize the remaining economy. Second, oil price innovations also lead to higher inflation in Azerbaijan. In response to the required tightening of monetary policy, the manat appreciates against the US dollar. Finally, GDP effects are primarily documented after oil price increases, whereas the interest rate and the exchange rate mainly react to decreases. Inflation increases after both types of shocks, either due to the accommodative monetary policy stance in the case of oil price decreases or due to the shock itself in the case of increases.
Keywords: E32; Q43; 330; Azerbaijan; Dutch disease; natural resources; oil prices; vector autoregression